ISOLATION OF THE COMPOUND MDMA FOR APPLICATION AS A REFERENCE MATERIAL (Revista Ifes Ciência, 2023)
In toxicological analyses, there is a significant need to utilize reference materials for the proper identification and quantification of suspicious samples, as well as for the identification of users of illicit drugs. In this regard, this study aimed to develop a methodology to isolate and purify the compound MDMA from seized "ecstasy" tablets by CP-ES (Civil Police of Espírito Santo) and subsequently characterize it using classical techniques such as high-resolution mass spectrometry by direct infusion, nuclear magnetic resonance, and finally, for purity evaluation, liquid chromatography technique. Based on the obtained results, a good yield in the isolation process, exceeding 90%, was achieved, with a calculated purity above 80%, affirming the proposed methodology as an attractive and accessible alternative for the isolation of the MDMA compound and its subsequent application in forensic analysis as a reference material.